Batch material for producing carbon-bonded products and method for producing carbon-bonded tiles
By using used refractory material batches with optimized particle size distribution in the production of carbon bonded refractory products, the problems of high thermal energy input and product properties are solved, and low energy consumption and high performance carbon bonded refractory products are achieved.
Patent Information
- Application Number
- CN202380042990.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-20
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-07
AI Technical Summary
The production process of existing carbon-bonded refractory products requires high heat energy input, resulting in high costs and greenhouse gas emissions. The use of recycled used refractory materials will lead to deterioration in the product properties and cannot meet application needs.
The batch containing used refractory materials with carbon bonds and carbon bonds is used. By adjusting their particle size distribution, the particle size of used refractory materials with carbon bonds is relatively coarse, and the particle size of used refractory materials without carbon bonds is relatively fine. This reduces heat energy input and improves product properties.
It realizes the production of carbon-bonded refractory products with good refractory properties under low heat energy input, which is suitable for standard applications, improves density and cold crushing strength, and avoids deterioration of product properties.
Abstract
Description
[0001] The present invention relates to a batch material for producing a carbon-bonded product and a method for producing a carbon-bonded product.
[0002] Carbon bonded products are known, in particular in the form of carbon bonded refractory bricks, ie bricks having a carbon bond and exposed to high temperatures during their use. A typical application of such carbon bonded refractory bricks is their use in metallurgical plants for the production and processing of molten steel, for example.
[0003] When manufacturing carbon bonded refractory products, a batch comprising a refractory component, a carbon component and an organic binder is generally used. The refractory component comprises one or more refractory raw materials, such as magnesia-based raw materials or alumina-based raw materials. The carbon component is a carrier of free carbon and is used to form carbon bonds. Typical carbon components are based on graphite. On the one hand, the organic binder provides batch green strength. On the other hand, the organic binder can also participate in the formation of carbon bonds.
[0004] The batch material comprising the above components is heated to a temperature at which carbon bonds are formed by the carbon component and the organic binder. After firing, a carbon-bonded refractory product is obtained.
[0005] The production of refractory raw materials constituting refractory components is energy intensive. In particular, these raw materials are usually produced with high heat energy input. On the one hand, this high heat energy input is disadvantageous for economic reasons, because it is particularly associated with high costs. On the other hand, high heat energy input is also disadvantageous especially for ecological reasons, since it is inevitably associated with the formation of large amounts of carbon dioxide. However, this carbon dioxide is released into the atmosphere, where it contributes to the greenhouse effect.
[0006] The typical refractory raw material for refractory components is magnesia, i.e., a refractory material composed mainly of magnesium oxide.
[0007] (MgO). The main source for producing magnesia is magnesite, i.e. magnesium carbonate (MgCO3). In order to produce magnesia from magnesite, it must be calcined, which requires heating the magnesite to temperatures above 1,700°C, which involves a large amount of thermal energy input.
[0008] Therefore, for ecological and economic reasons, attempts have been made in the past to reduce the thermal energy input required to provide batch materials for producing carbon-bonded refractory materials.
[0009] For example, attempts have been made to recycle spent carbon-bonded refractory materials or to reuse them in the manufacture of new carbon-bonded refractory products. In particular, the advantage of using spent refractory materials with carbon bonds as refractory components is that such materials can be obtained with much lower thermal energy input. This is because many thermal processes involving large energy inputs (such as the calcination of magnesite mentioned above) do not have to be used again to provide such spent refractory materials.
[0010] However, the use of spent refractory materials with carbon bonds as raw materials for the production of new carbon-bonded refractory products has proven to be extremely problematic. This is because the properties of carbon-bonded refractory products produced based on such spent refractory materials with carbon bonds are greatly degraded compared to the properties of carbon-bonded refractory products manufactured without such spent refractory materials. In some cases, the properties are so poor that the products produced cannot be used for any useful purpose.
[0011] An object of the present invention is to provide a batch material for producing carbon-bonded refractory products which can provide a low energy (especially thermal energy) input to its components. In particular, it should be possible to provide a lower energy input to the components than is possible with batch materials known from the prior art.
[0012] In particular, it is an object of the present invention to provide a batch material which comprises used refractory material having carbon bonds and from which a carbon-bonded refractory product having good refractory properties can be produced.
[0013] In particular, it is an object of the present invention to provide a batch material which can contain a relatively high proportion of spent refractory material having carbon bonds and from which carbon-bonded refractory products having good or at least still acceptable refractory properties can be produced.
[0014] In order to solve this problem, according to the present invention, a batch material for producing a carbon-bonded refractory product is provided, which comprises the following components:
[0015] refractory components; and
[0016] Organic binder; wherein
[0017] The refractory component comprises at least one used refractory material having carbon bonds and at least one used refractory material not having carbon bonds; wherein
[0018] The at least one spent refractory material having carbon bonds has a particle size distribution having a first d50 value; and
[0019] The particle size distribution of the at least one spent refractory material having no carbon bonds has a second d50 value; and wherein
[0020] The first d50 value is higher than the second d50 value.
[0021] The present invention is based in particular on the finding according to the invention that the refractory properties of a carbon-bonded refractory product may deteriorate, in particular if the batch used to produce the product contains only spent refractory material with carbon bonds in the fine fraction. According to the invention, it has now been recognized that the properties of a carbon-bonded refractory product produced from spent refractory material can be improved if the fine fraction of the batch contains a portion of spent refractory material without carbon bonds. Furthermore, according to the invention, it turns out that for the production of carbon-bonded refractory products, the use of spent material without carbon bonds in the fines results in properties similar to the use of natural (i.e., unused) material without carbon bonds in the fines.
[0022] The basic refractory component of the batch according to the present invention comprises at least one used refractory material with carbon bonds and at least one used refractory material without carbon bonds. The particle size distribution of at least one used refractory material with carbon bonds has a first d50 value, and the particle size distribution of at least one used refractory material without carbon bonds has a second d50 value. Thus, according to the present invention, the first d50 value is higher than the second d50 value. Therefore, the used refractory material with carbon bonds is "coarser" with respect to its particle size distribution, while the used refractory material without carbon bonds is therefore "finer".
[0023] As is known in the art, the d50 value indicates the particle size of a particle mixture, wherein 50% by mass of the particle mixture has a particle size of and below the d50 value and 50% by mass of the particle mixture has a particle size above the d50 value.
[0024] Thus, the first d50 value indicates that 50% by mass of the at least one used refractory material with carbon bonds has a particle size according to the first d50 value and below, and 50% by mass of the at least one used refractory material with carbon bonds has a particle size above the first d50 value, the mass fractions being in each case based on the total mass of the at least one used refractory material with carbon bonds.
[0025] Thus, the second d50 value indicates that 50% by mass of the at least one used refractory material containing no carbon bonds has a particle size according to the second d50 value and below, and 50% by mass of the at least one used refractory material containing no carbon bonds has a particle size above the second d50 value, the mass fractions being in each case based on the total mass of the at least one used refractory material containing no carbon bonds.
[0026] The criterion for determining the d50 value depends on the particle size of the particle fraction for which the d50 value is to be determined. If the particle fraction does not contain particles with a particle size greater than 1,000 μm, the d50 value is determined by laser diffraction in accordance with standard ISO 13320:2020-1 "Particle size analysis - Laser diffraction method". If the particle fraction contains particles with a particle size greater than 1,000 μm, the d50 value is determined by sieving in accordance with standard DIN EN 1402-3. Of course, if the particle fraction contains particles with a particle size greater than and less than 1,000 μm, the two standards can be combined with each other to determine the d50 value. Preferably, the d50 value of at least one used refractory material having carbon bonds is determined by sieving in accordance with standard DIN EN 1402-3, and the d50 value of at least one used refractory material without carbon bonds is determined by laser diffraction in accordance with standard ISO 13320:2020-1.
[0027] Surprisingly, it was found according to the present invention that based on the batch material according to the present invention, carbon-bonded refractory products can be produced whose refractory properties are good and still acceptable, so that they can be used for most standard applications of carbon-bonded refractory products. In particular, the density and cold crushing strength of such carbon-bonded refractory products are good and acceptable. In particular, the density and cold crushing strength of such carbon-bonded refractory products produced based on the batch material according to the present invention can be improved compared to products produced entirely from used materials with carbon bonds.
[0028] The carbon-bonded refractory product producible from the batch material according to the invention may in principle represent any carbon-bonded refractory product, preferably a shaped carbon-bonded refractory product, particularly preferably a carbon-bonded refractory brick.
[0029] Batch materials according to the present invention are used to produce carbon-bonded refractory products. The carbon bond can be formed by the carbon contained in the batch material according to the present invention. One source of this carbon is the carbon content of used refractory materials with carbon bonds. Another source of carbon can be an organic binder. Another source of carbon can be another carbon-based component that the batch material can also contain, as discussed further below.
[0030] In the sense of the present invention, a "used" refractory is a refractory that is a second raw material, i.e. a refractory that has been used for its original purpose and is now reused for another purpose, i.e. for providing a batch material according to the invention. In this respect, the batch material according to the invention is a recyclate. Thus, providing a batch material according to the invention or a method for producing a batch material according to the invention is recycling. This applies in particular because the used refractory products provided to the batch material according to the invention, which have not been used in the context of the present invention, represent waste and are now used for new purposes according to the invention in the context of recycling.
[0031] The original purpose of the used refractory material with or without carbon bonds may be its use in industrial high-temperature aggregates, in particular for the treatment of metal or glass melts. The industrial high-temperature aggregate for the treatment of molten metals may be in particular metallurgical equipment. The industrial high-temperature aggregate for the treatment of molten glass may be in particular glass tanks. The used refractory material with carbon bonds may particularly preferably be a material that has been used in metallurgical equipment. The used refractory material without carbon bonds may preferably be a material that has been used in a steel mill, preferably in the safety lining of, for example, a converter, a ladle or an electric arc furnace.
[0032] According to the present invention, it has been found that the refractory properties of the carbon-bonded refractory product producible from the batch material according to the present invention can be improved if the first d50 value is significantly higher than the second d50 value. According to a preferred embodiment, a first d50 value of at least 4 times, more preferably at least 10 times, more preferably at least 20 times, and even more preferably at least 30 times the second d50 value is provided. According to a further development of the inventive concept, a first d50 value of 4-150 times the second d50 value is provided, more preferably a range of 10-150 times, more preferably a range of 20-150 times, and even more preferably a range of 30-100 times.
[0033] Preferably, at least one refractory material having carbon bonds is provided to be present in a relatively coarse grain size. According to a preferred embodiment, a first d50 value is provided to be at least 500 μm, and particularly preferably in the range of 500 μm to 3,000 μm. Preferably, at least one refractory material without carbon bonds is provided to be present in a small grain size or in a fine grain size, respectively. According to a preferred embodiment, a second d50 value is provided to be not more than 400 μm, and according to a further development of the invention, in the range of 10 μm to 400 μm, and even more preferably in the range of 30 μm to 100 μm.
[0034] According to one embodiment of the present invention, it is provided that the mass percentage of particles of the at least one used refractory material having carbon bonds having a particle size below the second d50 value is less than the mass percentage of particles of the at least one used refractory material without carbon bonds having a particle size below the second d50 value, each mass percentage being based on the total mass of the refractory component.
[0035] Preferably, the at least one refractory material having carbon bonds is present in the refractory component at a greater mass percentage than the at least one spent refractory material not having carbon bonds.
[0036] According to one embodiment, it is provided that the at least one used refractory material having a carbon bond exists in a ratio of 80-99 mass % range, and the at least one used refractory material without a carbon bond exists in a ratio of 1-20 mass % range, each based on the total mass of the refractory component. More preferably, it is provided that the at least one used refractory material having a carbon bond exists in a ratio of 85-95 mass % range, and the at least one used refractory material without a carbon bond exists in a ratio of 5-15 mass % range, each based on the total mass of the refractory component.
[0037] The at least one used refractory material having carbon bonds can in principle be present in the form of any used refractory material having carbon bonds known from the prior art.
[0038] According to a preferred embodiment, it is provided that the at least one used refractory material having carbon bonds consists of at least one of: a used carbon-bonded magnesia-based refractory material and a used carbon-bonded alumina-magnesia-based refractory material.
[0039] Used carbon-bonded magnesia-based refractory is a used carbon-bonded refractory based on magnesia. Particularly preferred are carbon-bonded magnesia bricks, i.e., so-called MgO-C bricks. Preferably, the chemical composition of the used carbon-bonded magnesia-based refractory has at least 50 mass % of MgO, further preferably at least 80 mass % of MgO, and still further preferably at least 90 mass % of MgO. Preferably, the proportion of other oxides is lower than 50 mass %, more preferably lower than 20 mass %, and even more preferably lower than 10 mass %. Preferably, the proportion of MgO is in the range of 50-99 mass % and the proportion of other oxides is in the range of 1-50 mass %, more preferably the proportion of MgO is in the range of 80-99 mass % and the proportion of other oxides is in the range of 1-20 mass %, and even more preferably the proportion of MgO is in the range of 90-99 mass % and the proportion of other oxides is in the range of 1-10 mass %. The other oxides are preferably at least one of the following oxides: Al2O3, CaO and SiO2. The above data in mass % are based on the total mass of the used carbon-bonded magnesia-based refractory material.
[0040] The used carbon-bonded alumina-magnesia based refractory is a used carbon-bonded refractory based on magnesia and alumina. In addition or as an alternative, the used carbon-bonded alumina-magnesia based refractory may be a used carbon-bonded refractory based on magnesia, alumina and spinel (i.e. MgO, Al2O3 or MgAl2O4). Particularly preferred are carbon-bonded alumina-magnesia-carbon bricks, i.e. so-called AMC bricks. Preferably, the chemical composition of the used carbon-bonded alumina-magnesia based refractory has at least 50% by mass of MgO and Al2O3, further preferably at least 80% by mass of MgO and Al2O3, and still further preferably at least 90% by mass of MgO and Al2O3. Preferably, the proportion of other oxides is lower than 50% by mass, more preferably lower than 20% by mass, and even more preferably lower than 10% by mass. Preferably, the ratio of MgO to Al2O3 is in the range of 50-99 mass % and the ratio of other oxides is in the range of 1-50 mass %, more preferably the ratio of MgO to Al2O3 is in the range of 80-99 mass % and the ratio of other oxides is in the range of 1-20 mass %, and even more preferably the ratio of MgO to Al2O3 is in the range of 90-99 mass % and the ratio of other oxides is in the range of 1-10 mass %. The other oxides are preferably at least one of the following oxides: CaO and SiO2. The above data in mass % are based on the total mass of the used carbon-bonded alumina-magnesia-based refractory material.
[0041] At least one used carbon-bonded refractory material, in particular the used carbon-bonded refractory material described above, may have a conventional carbon ratio known in the prior art, for example, based on the total mass of the used carbon-bonded refractory material, the carbon ratio is in the range of 1-15 mass %. These carbon fractions are not included in the mass fractions of the above oxides, because when determining the oxide fractions, they represent the ignition loss.
[0042] According to a preferred embodiment, the at least one used refractory material not containing carbon bonds consists of at least one of: a used magnesia-based refractory material and a used alumina-magnesia-based refractory material.
[0043] The used magnesia-based refractory material may generally be any used magnesia-based refractory material known in the prior art which does not contain carbon bonds. Preferably, it is a sintered used magnesia-based refractory material. Particularly preferably, the used magnesia-based refractory material is a sintered used magnesia-based refractory brick. Preferably, the chemical composition of the used magnesia-based refractory material may correspond to the chemical composition of the used carbon-bonded magnesia-based refractory material described above.
[0044] The used alumina-magnesia based refractory material may generally be any used alumina-magnesia based refractory material known in the prior art which does not contain carbon bonds, for example spinel (MgAl2O4). Preferably, it is a sintered used alumina-magnesia based refractory material. Particularly preferably, the used alumina-magnesia based refractory material is a sintered used alumina-magnesia refractory brick. Preferably, the chemical composition of the used alumina-magnesia based refractory material may correspond to the chemical composition of the used carbon-bonded alumina-magnesia based refractory material described above.
[0045] According to a preferred embodiment, the at least one used refractory material having carbon bonds consists of at least one of: a magnesia-based refractory material having carbon bonds and an alumina-magnesia-based refractory material having carbon bonds; and wherein the at least one used refractory material not containing carbon bonds consists of a magnesia-based refractory material not containing carbon bonds and an alumina-magnesia-based refractory material not containing carbon bonds.
[0046] According to a particularly preferred embodiment, the at least one used refractory material having carbon bonds is a magnesia-based refractory material having carbon bonds; and wherein the at least one used refractory material not containing carbon bonds is a magnesia-based refractory material not containing carbon bonds.
[0047] According to one embodiment, the at least one used refractory material having carbon bonds is a calcined dolomite-based refractory material having carbon bonds; and wherein the at least one used refractory material not containing carbon bonds is at least one of: a calcined dolomite-based refractory material not containing carbon bonds and a magnesia-based refractory material not containing carbon bonds.
[0048] According to one embodiment, the refractory component of the batch according to the invention consists exclusively of at least one used refractory material having carbon bonds and at least one used refractory material not containing carbon bonds.
[0049] With regard to its chemical composition, the batch according to the invention is preferably magnesia-based, i.e. essentially based on MgO. According to one embodiment, it is provided that the batch comprises at least 50% by mass of MgO, more preferably at least 80% by mass of MgO, and even more preferably at least 90% by mass of MgO. It is further preferably provided that the batch comprises up to 50% by mass of other oxides, more preferably up to 20% by mass, and even more preferably up to 10% by mass of other oxides. According to one embodiment, it is provided that the batch comprises 50-99% by mass of MgO and 1-50% by mass of other oxides, more preferably 80-99% by mass of MgO and 1-20% by mass of other oxides, and even more preferably 90-99% by mass of MgO and 1-10% by mass of other oxides, in each case based on the total mass of the batch. The other oxides are preferably at least one of Al2O3, CaO and SiO2.
[0050] When a chemical composition is given in this application, it was determined by XRF according to standard ISO 12677.
[0051] According to the invention, it has surprisingly turned out that the batch according to the invention can contain a relatively high proportion of spent refractory material with carbon bonds, whereby a carbon-bonded refractory product with acceptable refractory properties can be produced from the batch. Thus, it can be provided that the batch according to the invention contains at least one spent refractory material with carbon bonds in a proportion of at least 80% by mass, or even in a proportion of at least 90% by mass, based on the total mass of the refractory component.
[0052] The batch material according to the present invention may further preferably comprise a carbon-based component of a batch material for producing a carbon-bonded refractory product as known in the prior art. The carbon-based component may comprise at least one carbon-based raw material. Preferably, the carbon-based component comprises a carbon-based raw material in the form of graphite, particularly preferably in the form of flake graphite.
[0053] According to one embodiment, the batch material contains carbon-based components, each in a proportion of 1 to 15% by mass, and more preferably in a proportion of 2 to 10% by mass, based on the total mass of the batch material.
[0054] The organic binder may be in the form of at least one binder known in the prior art for use in the production of batches of carbon-bonded refractory products. Preferably, the organic binder is in the form of at least one of the following organic binders: bitumen or a synthetic resin. The organic binder in the form of a synthetic resin is most preferably in the form of a phenolic resin.
[0055] Preferably, the organic binder is present in a proportion in the range from 1 to 10% by mass, more preferably in a proportion in the range from 2 to 7% by mass, based in each case on the total mass of the batch without organic binder.
[0056] According to a preferred embodiment, it is provided that the organic binder is in the form of a synthetic resin and comprises lignin. Surprisingly, according to the present invention, it has been found that a carbon-bonded refractory product can be produced by a batch comprising an organic binder in the form of lignin. It is known that a binder comprising lignin is a temporary binder for a refractory batch, but is not a temporary binder for a refractory batch for producing a carbon-bonded product. Surprisingly, according to the present invention, it has now been found that a batch for producing a carbon-bonded refractory product can also comprise a binder in the form of lignin. The advantage of an organic binder comprising lignin is particularly that the energy balance of the batch according to the present invention can be further improved. This is because lignin can be obtained as waste from papermaking or as a renewable raw material. In this regard, the organic binder of the batch according to the present invention can be partially replaced by lignin. Within this scope, it must be taken into account that the binder (particularly phenolic resin) used in the batch for producing a carbon-bonded refractory product must be produced as the main raw material with high energy input. By having an organic binder comprising lignin, the energy input of the batch according to the present invention can be further improved.
[0057] Preferably, the organic binder comprises at least 10% by mass of lignin, based on the total mass of the organic binder. It has been found that the organic binder cannot be completely replaced by lignin, because if the batch only comprises the organic binder in the form of lignin, the properties of the carbon-bonded refractory product made from such a batch will deteriorate. According to a preferred embodiment, therefore, based on the total mass of the organic binder, there is provided a lignin in a ratio in the range of 10-50% by mass of the organic binder. Preferably, the organic binder comprises 10-50% by mass of lignin and 50-90% by mass of phenolic resin, each based on the total mass of the organic binder.
[0058] As is known in the art, the batch material according to the present invention may further comprise any antioxidant, such as powder of metallic aluminum, silicon or alloys thereof.
[0059] It is also an object of the present invention to provide a method for producing a carbon-bonded refractory product comprising the following steps:
[0060] Providing a batch material according to the present invention;
[0061] The batch is subjected to a temperature to produce a carbon bonded refractory product.
[0062] Preferably, the batch is subjected to a temperature at which the carbon components in the batch coke and thereby form carbon bonds. Preferably, the batch is subjected to a temperature in the range of 200-350° C. At temperatures within this temperature range, the carbon components in the batch may coke and thereby form carbon bonds. The temperature may come from the process heat used.
[0063] Before the batch is subjected to a certain temperature, the batch may preferably be shaped, preferably by pressing. Preferably, the batch is shaped (especially by pressing) into a green body. The carbon-bonded refractory brick is made from the green body by subsequently subjecting the green body to a certain temperature.
[0064] Before the batch is subjected to a certain temperature, and to the extent that the batch should be formed, before pressing, the batch is preferably mixed to homogenize the batch. Preferably, the batch can be mixed in a mixer.
[0065] In all other respects, the carbon-bonded refractory products can be prepared from the batch material according to the invention by techniques known in the art.
[0066] As mentioned above, at least one used refractory material having carbon bonds may in particular represent a refractory material that is already in the aggregate for processing the molten metal. According to one embodiment, the following process steps may therefore be provided before the process step of providing the batch material:
[0067] A used refractory material having a carbon bond is separated from at least one aggregate material used to process molten metal and then provided to provide the at least one used refractory material having a carbon bond.
[0068] In addition, as described above, at least one used refractory material without carbon bonds can represent a refractory material that has been used in the aggregate for processing molten metal or molten glass. According to one embodiment, the following process steps can therefore be provided before the process step of providing the batch material:
[0069] A used refractory material free of carbon bonds is separated from at least one aggregate for treating molten metal or for treating glass melt, and then the separated used refractory material is provided to provide the at least one used refractory material free of carbon bonds.
[0070] As described above, it has surprisingly been found that carbon-bonded refractory products having acceptable refractory properties can be produced from the batch material according to the invention, in particular even if the batch material contains a relatively high proportion of spent refractory material having carbon bonds. Within this range, it has been found that carbon-bonded refractory products having acceptable density and acceptable cold crushing strength can be produced. If the density after coking the batch material at 1,000°C is at least 2.70 g / cm 3 The density is considered acceptable if the cold crushing strength is at least 20 MPa after coking the batch at 1,000°C.
[0071] The carbon bonded refractory product according to the invention may be used, for example, in a ladle or an electric arc furnace.
[0072] Further features of the invention will be apparent from the invention claims and the following exemplary embodiments.
[0073] All features of the invention may be combined individually or in any desired combination.
[0074] The present invention is explained in more detail with reference to the following exemplary embodiments:
[0075] Exemplary embodiments
[0076] In a first step, spent refractory material having carbon bonds and spent refractory material without carbon bonds are separated from a furnace of a metallurgical installation.
[0077] The used refractory material with carbon bonds is in the form of used carbon-bonded magnesia bricks (i.e., so-called MgO-C bricks), whose chemical composition is 94.0% by mass of MgO and 6.0% by mass of other oxides, in particular Al2O3, CaO and SiO2.
[0078] The used carbon-bonded magnesia brick further contained carbon in an amount of 14.0 mass % based on the total mass of the used carbon-bonded refractory material. These carbon fractions are not included in the mass fractions of the above oxides because they represent the loss on ignition when determining the oxide fractions.
[0079] The used refractory material containing no carbon bonds is a sintered used magnesia refractory brick having a chemical composition of 94.0% by mass of MgO and 6.0% by mass of other oxides, in particular Al2O3, CaO and SiO2.
[0080] All the above chemical compositions (ie oxides) were determined by XRF according to standard ISO 12677 (with reference to the fired samples, ie without reference to the carbon content).
[0081] The spent refractory material with carbon bonds is crushed into a particle size in the range of >0-5 mm and provided as a particle fraction of >0-2 mm and a particle fraction of >2-5 mm. The sintered spent magnesia refractory bricks are further crushed and provided as a particle size of >0-1 mm.
[0082] Below, a batch material for producing carbon bonded magnesia bricks is provided.
[0083] Thus, the above identified used carbon bonded magnesia bricks crushed to the above mentioned particle size have been provided as used refractory material with carbon bonds within the meaning of the present invention. In the following Table 1, this material is indicated as "used refractory material with C bonds".
[0084] In addition, the above identified sintered used magnesia refractory bricks crushed to the above mentioned particle size have been provided as used refractory material without carbon bonds within the meaning of the present invention. In the following Table 1, this material is indicated as "used refractory material without C bonds".
[0085] In Table 1 below, the formulations of two batches are given, one of which is designated A and the second batch B. The proportions of the individual components of batches A and B indicated in the first column of Table 1 are given in % by mass, in each case based on the total mass of the respective batch.
[0086] Components Batch "A" Batch "B" Used refractory with C bond (>2-5mm) 36 37 Used refractory with C bond (>0-2mm) 40 48 Used refractory materials without C bonds (>0-1mm) 11 - graphite 8 10 asphalt 3 3 Other components 2 2
[0087] Table 1
[0088] Batch A represents an exemplary embodiment of a batch according to the invention. The refractory component consists of used carbon-bonded magnesia bricks with a particle fraction > 0-2 and 2-5 mm ("used refractory material with C bonds") and sintered used magnesia refractory bricks with a particle fraction > 0-1 mm ("used refractory material without C bonds"). Pitch is used as an organic binder. In addition, the batch contains a carbon-based component in the form of graphite (flake graphite).
[0089] Batch B is essentially the same as Batch A. The main difference is that Batch B does not contain a component in the form of sintered used magnesia refractory bricks ("used refractory without C bonds"). Instead, Batch B contains a higher proportion of used carbon-bonded magnesia bricks ("used refractory with C bonds") with a finer particle fraction > 0-2 mm.
[0090] The d50 value of used carbon-bonded magnesia bricks with a particle fraction >2-5 mm ("used refractory material with C bonds") was measured by sieving according to standard DIN EN 1402-3 and was determined to be 3,150 μm.
[0091] The d50 value of used carbon-bonded magnesia bricks with a particle fraction > 0-2 mm ("used refractory material with C bonds") was measured by sieving according to standard DIN EN 1402-3 and was determined to be 700 μm.
[0092] The d50 value of used carbon-bonded magnesia bricks with a total particle fraction > 0-5 mm ("used refractory material with C bonds") was measured by sieving according to standard DIN EN 1402-3 and was determined to be 2,000 μm.
[0093] The d50 value of sintered used magnesia refractory bricks ("used refractory material without C bonds") was measured by laser diffraction according to standard ISO 13320:2020-1 and was determined to be 500 μm.
[0094] Thus, the refractory components of Batches A and B each have substantially matching particle size distributions.
[0095] The chemical composition of batches A and B was determined by XRF according to standard ISO 12677 and was determined as shown in Table 2.
[0096] Oxide Batch "A" Batch "B" MgO 94.1 94.0 <![CDATA[Al2O3]]> 1.2 1.5 CaO 1.8 1.8 <![CDATA[SiO2]]> 1.4 1.5 other 1.5 1.2
[0097] Table 2
[0098] To produce carbon-bonded magnesia bricks from batches A and B, the batches were mixed in a mixer, pressed into green compacts and finally coked by subjecting the green compacts to a temperature of 200° C. for six hours, which temperature came from the process heat used. Carbon-bonded magnesia bricks were then provided.
[0099] In order to determine whether the carbon-bonded magnesia bricks obtained from batches A and B had acceptable refractory properties, the density was measured according to DIN EN 993-1 and the cold crushing strength was measured according to DIN EN 993-5 after coking at 1,000° C. The values for the bricks obtained from batch A (“brick A”) and the bricks obtained from batch B (“brick B”) are given in Table 3 below.
[0100] nature Brick A Brick <![CDATA[Density [g / cm 3 > 2.72 2.68 Cold crushing strength[MPa] 20 18
[0101] Table 3
[0102] It can be seen that Brick A has both a higher density and a significantly higher cold crushing strength than Brick B.
[0103] In summary, although Brick A has a higher percentage of spent refractory material than Brick B, the refractory value of Brick A is still acceptable as opposed to the refractory value of Brick B.
Claims
1. A batch material for producing a carbon-bonded refractory product comprising the following components: 1.1 refractory components; and 1.2 Organic binder; 1.3 The refractory components include 1.3.1 At least one spent refractory material having a carbon bond and 1.3.2 At least one used refractory material that does not contain carbon bonds; 1.4 the particle size distribution of the at least one used refractory material having carbon bonds has a first d50 value; and 1.5 The particle size distribution of the at least one used refractory material containing no carbon bonds has a second d50 value; and wherein 1.6 the first d50 value is higher than the second d50 value; and wherein 1.7 The at least one used refractory material having a carbon bond is present in a proportion ranging from 80-99 mass %, and the at least one used refractory material not containing a carbon bond is present in a proportion ranging from 1-20 mass %, each based on the total mass of the refractory component.
2. The batch material of claim 1, wherein the first d50 value is at least 4 times the second d50 value.
3. Batch according to at least one of the preceding claims, wherein the first d50 value is at least 500 μm.
4. Batch according to at least one of the preceding claims, wherein the second d50 value is not higher than 400 μm.
5. The batch material according to at least one of the preceding claims, wherein the at least one used refractory material having a carbon bond consists of at least one of: a used carbon-bonded magnesia-based refractory material and a used carbon-bonded alumina-magnesia-based refractory material.
6. The batch material according to at least one of the preceding claims, wherein the at least one used refractory material free of carbon bonds consists of at least one of: a used magnesia-based refractory material and a used alumina-magnesia-based refractory material.
7. The batch according to at least one of the preceding claims, wherein The at least one used refractory material having carbon bonds consists of at least one of: a magnesia-based refractory material having carbon bonds and an alumina-magnesia-based refractory material having carbon bonds; and wherein The at least one used refractory material not containing carbon bonds consists of a magnesia-based refractory material not containing carbon bonds and an alumina-magnesia-based refractory material not containing carbon bonds.
8. The batch material according to at least one of the preceding claims, wherein the batch material further comprises a carbon-based component.
9. The batch material of claim 8, wherein the carbon-based component is in the form of graphite.
10. Batch material according to at least one of the preceding claims, wherein the organic binder is bitumen.
11. The batch material according to at least one of claims 1 to 9, wherein the organic binder comprises lignin.
12. The batch material according to claim 11, wherein the organic binder comprises at least 10 mass% of lignin based on the total mass of the organic binder.
13. A method for producing a carbon bonded refractory product comprising the steps of: A. Providing a batch according to at least one of the preceding claims; B. Subjecting the batch to a temperature to produce a carbon-bonded refractory product.
14. The method according to claim 13 further comprises the step of separating the used refractory material having a carbon bond from at least one aggregate for processing molten metal and then providing the separated used refractory material to provide the at least one used refractory material having a carbon bond.